2015
DOI: 10.1097/fjc.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ivabradine on Heart Rate and Duration of Exercise in Patients With Mild-to-Moderate Mitral Stenosis

Abstract: Background:Symptoms in mitral stenosis (MS) are heart rate (HR) dependent. Increase in HR reduces diastolic filling period with rise in transmitral gradient. By reducing HR, beta-blockers improve hemodynamics and relieve symptoms, but the use may be limited by side effects. The present randomized crossover study looked at comparative efficacy of ivabradine and metoprolol on symptoms, hemodynamics, and exercise parameters in patients with mild-to-moderate MS (mitral valve area, 1–2 cm2) in normal sinus rhythm.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This is in contrast to the earlier meta-analysis by Adviento et al [ 20 ], where ivabradine was not significantly different to beta-blocker with regards to these clinical parameters. Individually, the included studies [ 17 - 19 ] showed that ivabradine and beta-blockers were able to similarly improve these outcomes, but in our study, it appears that ivabradine is in fact better. Dhanger [ 21 ] was able to show a statistically significant improvement in exercise duration from baseline among symptomatic MS patients in sinus rhythm, when treated with ivabradine for 3 months.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This is in contrast to the earlier meta-analysis by Adviento et al [ 20 ], where ivabradine was not significantly different to beta-blocker with regards to these clinical parameters. Individually, the included studies [ 17 - 19 ] showed that ivabradine and beta-blockers were able to similarly improve these outcomes, but in our study, it appears that ivabradine is in fact better. Dhanger [ 21 ] was able to show a statistically significant improvement in exercise duration from baseline among symptomatic MS patients in sinus rhythm, when treated with ivabradine for 3 months.…”
Section: Discussionmentioning
confidence: 46%
“…The severity of the mitral valve stenosis may play a role. For example, Dhanger [ 21 ] started at a baseline mean gradient of about 12 mm Hg, while Saggu [ 17 ] started at about 10 mm Hg. In both studies, ivabradine and beta-blocker both significantly improved mean gradient, but this slight difference in the hemodynamic severity of the lesions may have spelled the difference to achieving statistical significance between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies have evaluated the effects of HR reduction with ivabradine in patients with mild to moderate MS and normal sinus rhythm (Table 3). 58–64 In all studies, ivabradine showed a significant reduction in HR from baseline. Two studies showed significant benefits with ivabradine versus β‐blockers on exercise time and working capacity, respectively 58,62 .…”
Section: Resultsmentioning
confidence: 88%
“…In this issue of the Journal, Saggu et al 29 present data from a study that was designed to evaluate the cardiovascular effects of ivabradine as compared with metoprolol in patients with mild to moderate mitral stenosis. Although the study population was small, the results are more informative than the much larger multicenter studies because by using a crossover design and by titrating the doses of both ivabradine and metoprolol to a heart rate end point, the investigators eliminated the bias that occurred in the large trials because ivabradine was titrated to heart rate in the treatment group but the dose of the β-blocker was not titrated in the placebo group.…”
mentioning
confidence: 99%